2020
DOI: 10.1186/s12879-020-05309-8
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a simple antimicrobial stewardship intervention in general practice in Australia: a pilot study

Abstract: Background: Inappropriate and excessive antimicrobial prescribing can lead to antimicrobial resistance. Antimicrobial Stewardship (AMS) principles are not well established in general practice in Australia despite the relatively high rate of community antimicrobial prescribing. Few interventions have been implemented that have resulted in a significant reduction or improvement in antimicrobial prescribing by General Practitioners (GPs). This study was therefore conducted to assess the impact of a novel GP educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 32 publications
(43 reference statements)
0
23
0
Order By: Relevance
“…The quality improvement strategies have been fitted into a GPPAS model as key components. The Australian pilot study [26] of a GPPAS sub-model conducted in a general practice found that GP educational intervention facilitated by a team of physician and pharmacist was significantly effective in improving appropriateness in antimicrobial selection (73.9% vs 92.8%, RR = 1.26; 95% CI = 1.18-1.34), duration (53.1% vs 87.7%, RR = 1.65; 95% CI = 1.49-1.83) and guideline compliance (42.2% vs 58.5%, RR = 1.39, 95% CI = 1.19-1.61).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality improvement strategies have been fitted into a GPPAS model as key components. The Australian pilot study [26] of a GPPAS sub-model conducted in a general practice found that GP educational intervention facilitated by a team of physician and pharmacist was significantly effective in improving appropriateness in antimicrobial selection (73.9% vs 92.8%, RR = 1.26; 95% CI = 1.18-1.34), duration (53.1% vs 87.7%, RR = 1.65; 95% CI = 1.49-1.83) and guideline compliance (42.2% vs 58.5%, RR = 1.39, 95% CI = 1.19-1.61).…”
Section: Resultsmentioning
confidence: 99%
“…A GPPAS sub-model was well received, cost effective and showed potential for improving appropriateness and guideline compliance of antimicrobial prescribing by GPs in Australia [26]. Whether and how long these improvements sustained after ceasing GPPAS intervention is also worth exploring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be due to clinicians not referring to current guidelines, prescriber error and prescriber discomfort in using recommended high-dose amoxicillin regimens. 14 Further research is required regarding antibiotic prescribing for children with AOM in primary care; however, targeted education, access to Therapeutic Guidelines 15 and clinical decision support tools embedded in practice software prompting prescribers to weigh children and select an appropriate dosing regimen may promote optimal dosing for AOM in children.…”
Section: Sub-therapeutic Dosing In Acute Otitis Media In Childrenmentioning
confidence: 99%
“…Perhaps this issue is an added instigating force to the extensive and unnecessary prescribing, utilization, and prescription of antimicrobials 46,[61][62][63] . Multiple studies conducted globally have reported that educational antimicrobial stewardship intervention among health professionals have effectively reduced the imprudent consumption of antimicrobial [64][65][66] . Thereby, it decreases the incidence of hospitalacquired candidemia and the emergence of Multi-Drug Resistant (MDR) Blood Stream Infection (BSI) 64 .…”
Section: " Sir Alexander Flemingmentioning
confidence: 99%